SIDNEY SHELDON ONE OF THE FAMOUS AMERICAN WRITERS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Sidney Sheldon is one of the representatives of modern American literature. His works are very interesting and attract the readers. His novels were translated into 51 languages among them the Russian translations are also known to Uzbek readers.